On shifting the principal eigenvalue of Dirichlet problem to infinity with non-transversal incompressible drift - Athmouni, Nassim; Damak, Mondher; Franke, Brice; Yaakoubi, Nejib (MATHEMATICA SCANDINAVICA, 2023)
We prove that it is always possible to add some divergence free drift vector field to some two dimensional spherical Dirichlet problem, such that the resulting principal eigenvalue lies above a prescribed bound. By construction those drift vector fields vanish on the boundary and their flow lines individually stay away from the boundary. The capacity of those drift vector fields to accelerate diffusivity originates from high frequency oscillation of the associated flow lines. The lower bounds for the spectrum are obtained through isoperimetric inequalities for flow invariant functions.